Penyeimbangan Lintasan Produksi dengan Metode Heuristic Ranked Positional Weight dan Large Candidate Rule pada Lini Perakitan Printer - Imam Arief; Uly Amrina (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2022)
The mold and metal press work stations line assembly printerThere are several work stations that have a processing time that exceeds the takt time 3.66 minutes. The processing time that exceeds the takt time is at the Cassete 2 and Mechanism 1 work stations with respective times (4.74 minutes) and (4.75 minutes), while the Mechanism 2 work station is the lowest with time (1.2 minutes). . The purpose of this research is to balance the production assembly line the printerResearchers use the Heuristic Ranked Positional Weight (RPW) and Large Candidate Rule (LCR). Comparison of the results of the calculation of path efficiency, smoothing index and balance delay using these two methods shows that the RPW method is the most optimal method. This is indicated by the highest assembly line efficiency value of 89.34%, the balance delay of 10.66%, smoothing index of 5.2785 and the least number of work stations of 13. Thus this will make production run well and smoother than the initial condition. Keywords: Heuristic; Ranked Positional Weight (RPW); Large Candidate Rule (LCR); Line Efficiency; Balance Delay; Smoothing Index